PENGARUH PERSEPSI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI - Rahmawaty, Dian (Jurnal Benefita, 2017)
This research aims to examine and analyze the actual conditions of the company concerned with the perception of employees, organizational culture and work motivation as variables the moderation that ultimately have an impact on the performance of employees. This research was conducted against officers at public works city of Bukittinggi with number of employees as many as 76 people. Analysis of the method used is descriptive analysis with Moderated Regression Analysis use Analysis (MRA) by processing the data using SPSS ver. 16.0 for windows. Then conducted the analysis with the data using the test of validity, reliability, descriptive variable analysis (TCR), a Moderated Regression Analysis Analysis (MRA), the coefficient of determination and hypothesis testing so that it brings the equation Y=14,142-0,187X1+0,376X2+ 0,147Mo. From the results of the analysis shows that the regression coefficient of interaction between job motivation and perception is -0.05 and significant is 0,756. The significant value is greater than ɑ = 0.05. It can be interpreted that work motivation variable (Mo) does not moderate the influence of perception on employee performance and show negative influence. Thus the fourth hypothesis in this study that states work motivation moderate the influence of perceptions on employee performance declared rejected. Furthermore, the regression coefficient of interaction variable between organizational culture and work motivation is 0.012 and significant 0,341. The significant value is greater ɑ = 0.05.The results showed that the perception of the negative and not significant effect against the performance of employees on public works city of Bukittinggi. Organizational culture positive and significant effect on performance clerk on public works city of Bukittinggi. The motivation of working positively and significantly to the performance of employees on public works city of Bukittinggi. Penelitian ini bertujuan untuk mengkaji dan menganalisis kondisi sebenarnya dari perusahaan berkaitan dengan persepsi pegawai, budaya organisasi dan motivasi kerja sebagai variabel moderasi yang pada akhirnyaberdampak pada kinerja pegawai. Penelitian ini dilakukan terhadap pegawai pada Dinas Pekerjaan Umum Kota Bukittinggi dengan jumlah pegawai sebanyak 76 orang. Metode analisis yang digunakan adalah analisis deskriptif dengan menggunakan Analisis Moderated Regression Analysis (MRA). Analisis Moderated Regression Analysis (MRA), koefisien determinasi dan pengujian hipotesis sehingga didapatkan persamaan Y =14,142-0,187X1+0,376X2+0,147Mo. Dari hasil analisis tersebut terlihat bahwa besaran koefisien regresi variabel interaksi antara motivasi kerja dan persepsi adalah -0,05 dan signifikan sebesar 0,756. Nilai signifikan tersebut lebih besar dari ɑ = 0,05. Hal ini dapat diartikan bahwa variabel motivasi kerja (Mo) tidak memoderasi pengaruh persepsi terhadap kinerja pegawai  dan menunjukkan pengaruh yang negatif. Dengan demikian hipotesis keempat dalam penelitian ini yang menyatakan motivasi kerja memoderasi pengaruh persepsi terhadap kinerja pegawai dinyatakan ditolak.Selanjutnya besaran koefisien regresi variabel interaksi antara budaya organisasi dan motivasi kerja adalah 0,012 dan signifikan 0,341. Nilai signifikan tersebut lebih besar ɑ = 0,05. Hasil penelitian menunjukkan bahwa Persepsi berpengaruh negatif dan tidak signifikan terhadap kinerja pegawai pada Dinas Pekerjaan Umum Kota Bukittinggi. Budaya organisasi berpengaruh positif dan signifikan terhadap kinerja pegawai pada Dinas Pekerjaan Umum Kota Bukittinggi. Motivasi kerja positif dan signifikan terhadap kinerja pegawai pada Dinas Pekerjaan Umum Kota Bukittinggi.